2015
DOI: 10.1021/acscatal.5b01281
|View full text |Cite
|
Sign up to set email alerts
|

Easy Accommodation of Different Oxidation States in Iridium Oxide Nanoparticles with Different Hydration Degree as Water Oxidation Electrocatalysts

Abstract: In this paper, we present a comprehensive study on low hydration Ir/IrO 2 electrodes, made of an Ir core and an IrO 2 shell, that are designed and synthesized with an innovative, green approach, in order to have a higher surface/bulk ratio of Ir−O active centers. Three materials with different hydration degrees have been deeply investigated in terms of structure and microstructure by means of transmission electron microscopy (TEM) and synchrotron radiation techniques such as high-resolution (HR) and pair distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
120
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(139 citation statements)
references
References 50 publications
18
120
0
1
Order By: Relevance
“…Alternatively, it can be concluded that the mechanism proposed by Kötz et al [58] is not operative. Below we present a tentative mechanism of OER on hydrous and also compact iridium oxide electrodes, similar to those reported by Minguzzi et al [40,62] for the former, which explains the observed dissolution results. Based on the results from CVs and density functional theory (DFT) calculations, Steegstra et al [41] suggested a binuclear mechanism of OER with participation of neighbor Ir(V) cites.…”
Section: Oer From Hydrous Iridium Oxide Electrode and Related Dissolusupporting
confidence: 89%
“…Alternatively, it can be concluded that the mechanism proposed by Kötz et al [58] is not operative. Below we present a tentative mechanism of OER on hydrous and also compact iridium oxide electrodes, similar to those reported by Minguzzi et al [40,62] for the former, which explains the observed dissolution results. Based on the results from CVs and density functional theory (DFT) calculations, Steegstra et al [41] suggested a binuclear mechanism of OER with participation of neighbor Ir(V) cites.…”
Section: Oer From Hydrous Iridium Oxide Electrode and Related Dissolusupporting
confidence: 89%
“…Ir nanoparticles did not exhibit Ir oxide characteristics in cyclic voltammograms (III/IV transition) or a shoulder in OER tests (Figure 2c, IV/V transition), before or after durability. 31,[35][36][37][38] The impact on dissolutiondriven losses is also unclear, since only a small amount of dissolution occurred during accelerated stress tests at these potentials ( Figures 4e and 4f). In either case, potential cycling of Ir nanoparticles produced less severe losses than potential holds in durability tests at electrolyzer-relevant potentials (Figures 4a and 4c).…”
Section: Resultsmentioning
confidence: 99%
“…[13] They showedt hat the highest stability under potentiostatic conditions was achieved for ATO-supported Pt electrocatalysts. [38][39][40] Such issues in preparing and characterizing amorphous Ir oxide/hydroxides might explain the lack of attention they have received so far. [14] In addition to optimized catalyst morphology by dispersion of Ir particles on as uitable support, producingt he "right" chemicals tate of Ir is no less critical to the OER performance of the catalytic system.E arly electrochemical studies showed that metallici ridium is inefficient in OER and needs to be activated under oxidative conditions.…”
Section: Introductionmentioning
confidence: 99%